2005
DOI: 10.1097/01.rlu.0000178784.58278.36
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET Imaging in Pneumocystis carinii Pneumonia

Abstract: The authors present a case of a 26-year-old man, under investigation for Cushing syndrome, who presented acutely with a dry cough and fever. The blood tests were unremarkable apart from a moderate to severe leukopenia. Imaging tests were suggestive of an atypical pneumonia, which was proven to be Pneumocystis carinii pneumonia (PCP) on cytology examination of a bronchoalveolar lavage (BAL). The acute lung changes were demonstrated on a whole-body F-18 fluorodeoxyglucose (FDG) positron emission tomography (PET)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Similarly, in a clinical study, FDG uptake returned to normal levels after successful antifungal therapy for a lung abscess caused by candidal infection [48] and after therapy for Pneumocystis jiroveci pneumonia [49].…”
Section: Acute Infectious Processesmentioning
confidence: 99%
“…Similarly, in a clinical study, FDG uptake returned to normal levels after successful antifungal therapy for a lung abscess caused by candidal infection [48] and after therapy for Pneumocystis jiroveci pneumonia [49].…”
Section: Acute Infectious Processesmentioning
confidence: 99%
“…The results indicated the importance of FDG-PET in guiding the duration of treatment in most patients (n=8). The role of FDG-PET in monitoring therapeutic efficacy has also been described in the setting of invasive aspergillosis [53], candidal lung abscess following antifungal therapy [54], and Pneumocystis carinii pneumonia [55]. Similar promising results have been obtained in non-infectious inflammatory conditions also (discussed under each subheading).…”
Section: Therapeutic Response Monitoringmentioning
confidence: 73%
“…Traditionally, gallium scintigraphy is used to diagnose and monitor PCP, which often demonstrates diffuse pulmonary uptake. Published case reports suggested that FDG PET-CT might be preferred to gallium scintigraphy for PCP diagnosis and monitoring, due to its better resolution, higher target to background uptake, faster imaging time and lower radiation dose [70,71].…”
Section: Pneumocystis Pneumoniamentioning
confidence: 99%